Assessment of the level of knowledge regarding the intramuscular administration of medication among staff nurses - Ammu, Ammu; Kumar, Sai Sailesh; Bashetti, Srilatha (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Intramuscular injection is an everyday procedure which is not without its hazards. Although insuring bodies have pointed out that the lateral thigh is the least unsafe site for an IM injection. The commonly used sites in the adult are gluteal and deltoid muscle. The present study was undertaken to assess the level of knowledge related to intramuscular administration of medication among staff nurses. Material and Methods: 30 samples were selected and descriptive research approach was used in the study. The level of study was assessed using self-administered questionnaire. Results: 46.67 % had inadequate knowledge, 40% had moderate knowledge regarding g the administration of IM injection. Efforts were also made to find the association between the level of knowledge and selected demographic variables. There is significant association between knowledge and educational status and years of clinical experience. Conclusion: The present study assessed the knowledge of staff nurses regarding the administration of intramuscular (IM) medication and tries to find association between the level of knowledge and selected demographic variables. At the nd of the study, the investigators found that there is association between the level of knowledge, age, educational status and year of experience. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5 (2): 35-40